Repercussões sistêmicas da orquiectomia bilateral, em ratos - Denny Fabricio Magalhaes Veloso (2007)
This investigation belongs to a line of research, and its purpose was toevaluate the effects of hypogonadism secondary to orchiectomy on the organism of rats. 178 male Wistar rats were used. Of these, 54 were young (Y) and 124 were mature (M). These animals were divided into the following groups: Group 1 control, animals submitted only to incision and suture of the scrotum. Group 2 animals that underwent total bilateral orchiectomy. After the surgeries, studies were conducted to analyze different repercussions of the hypogonadism. In study A, the serum levels of free testosterone, body weight and cortical size of the adrenal gland of 30 adult rats were measured. The data was obtained on the 30th postoperative day from 10 rats (Group 2i immediate) and in the 8th postoperative month. The 20 rats, of this study, were divided into Group 1 (n = 10) and Group 2l late (n = 10). In study B, the serum levels of glucose, triglycerides, total cholesterol and the HDL, LDL and VLDL fractions were measured five months after the surgeries in 40 rats. These animals were divided into Group 1Y (young, n = 10) and Group 1M (mature, n = 10) control and Group 2Y (young, n = 10) and Group 2M (mature, n = 10) submitted to bilateral orchiectomy. In study C, the physical capacity was evaluated based on the maximum running time on a treadmill during the 5th postoperative month in Group 1 (control, n = 5) and Group 2 (submitted to orchiectomy, n = 11). In study D, the pressure of caudal arteria assessed on 12 adult animals from Group 1 (control) and 12 adult animals from Group 2 (submitted to orchiectomy) was measured by a pletysmograph in the 3rd postoperative month. In study E, the function of the organs of the mononuclear phagocyte system was evaluated in the 7th postoperative month. 24 animals were divided intoGroups 1Y (young, n = 6), 1M (mature, n = 6) control and 2Y (young, n = 6) and 2M (mature, n = 6) submitted to orchiectomy. Sulfur colloid complexed with 99Tcm was injected and after one hour, samples were collected from the liver, spleen, lung and blood clots. The radioactivity of each sample was assessed. In study F, the resistance of scar tissue was measured in the 6th postoperative month. 44 rats were divided into Groups 1Y (young, n = 11), 1M (mature, n = 11) control and 2Y (young, n = 11) and 2M (mature, n = 11) submitted to orchiectomy. They underwent a median incision on the dorsum followed by suture of the surgical wound. On the 7th and 21st postoperative days after the surgical procedure, a fragment of skin, including a portion of the scar andthe healthy skin of both sides, was removed. The extremities of this fragment were grasped and the sample was then submitted to increasing traction. The resistance of the scar of each fragment was measured according to the traction value that provoked its rupture.The results revealed that total bilateral orchiectomy reduces the serumlevel of testosterone in rats regardless of the age and, apparently, does not alter the micro or macroscopic morphology of the adrenal gland. Hypogonadism secondary to total bilateral orchiectomy does not alter the serum levels of glucose, total cholesterol, HDL and LDL fractions. However, bilateral orchiectomy reduces the serum levels of triglycerides and VLDL cholesterol in young male rats. Testosterone deficiency is related to lower weight gain, increasing in blood pressure, reduction of initial phase of scar resistance. Orchiectomy did not affect the physical capacity of the rat and phagocyte function of the mononuclear phagocyte system. Therefore, the absence of testicular testosterone due to bilateralorchiectomy is followed by organical alterations and causes systemic functional disturbances.